Simulation-Based Computation of Information Rates for Channels With Memory - Arnold, D.M.; Loeliger, H.-A.; Vontobel, P.O.; Kavcic, A.; Wei Zeng (IEEE transactions on information theory, 2006)
The information rate of finite-state source/channel models can be accurately estimated by sampling both a long channel input sequence and the corresponding channel output sequence, followed by a forward sum-product recursion on the joint source/channel trellis. This method is extended to compute upper and lower bounds on the information rate of very general channels with memory by means of finite-state approximations. Further upper and lower bounds can be computed by reduced-state methods